Diversification and Characterization Taste of Tuna ‘Pucuk Meatballs’ with Caisim (Brassica Juncea L.) As the Natural Dye - Titien Sofiati; Risman; Asy’ari; Sandra Hi Muhammad; Djainudin Alwi (International Journal of Research in Vocational Studies (IJRVOCAS), 2023)
A fish has the natural perishable character because of the high concentration of water. The fish production have to be utilized in fast and accurate before the spoilage caused by the bacterial activity. One of the ways on utilizing fish is to be prepared as diversification products which is meatballs, and ect. The production of Tuna meatballs in Regency of Morotai Island is still in the standard level that probable to be improved. The improvement of the meatballs was made with the use of natural dye. One of the natural dye that can be used as food extraction (BTP) is Caisim (Brassica juncea L.). The purpose of this research is to create the meatballs product with Caisim (a kind of Chinese vegetable) and evaluate the product’s characteristics used the organoleptic test. The production was made at the Laboratory of Fisheries and Marine in University of Pacific Morotai. There were 50 untrained panelists. The result of this research is the diversification of Tuna meatballs with natural dye Caisim (Brassica juncea L) is successfully made and named with ‘Pucuk Meatballs’ (Bakso Pucuk). The Characteristics product of ‘Pucuk Meatballs’ has a smooth surface, not bladdery, and bright; the product’s specific fragrance; also, compact and rubbery texture.